Determination of the microbiological, physical-chemical and parasitological parameters of the water of drinking fountains present in a hospital unit in the Southwest of Bahia (Research, Society and Development, 2022)
The characteristics of water can be altered by the different components present on it, which can influence the physical, chemical, and biological parameters and determine its quality. In order to be suitable for human consumption, the water must be potable, and for this, constant surveillance must be carried out to meet the established standards of potability. This study aimed to determine the physical-chemical and microbiological parameters, as well as the parasitological analysis of water samples from drinking fountains in a private hospital in southwestern Bahia. The results obtained were compared with the parameters determined by the Ministry of Health (MH) with the justification of certifying a quality water provided in the hospital environment. This is a descriptive-exploratory study, with characteristics that are based on observation through quantitative and qualitative methods.  The use of these two methods allows more in-depth and comprehensive results of the reality under investigation, ensuring a better understanding of the problem under study. The analyses for the physical-chemical parameters met the potability standards established by Ordinance 2.914/2011 and were safe for the parasitological analyses. Regarding the microbiological analyses, the results are unsatisfactory because they point to the presence of coliforms in one of the samples studied.